Association Of Taqi Polymorphism of Vitamin D Receptor (VDR) Gene with Anemia in Saudi Women - AL-Ghamdi, Maryam A. (Journal of Contemporary Medical Sciences, 2022)
Objective: This study aims to correlate occurrence of anemia in a population of Saudi women with polymorphisms in the VDR gene. Methods: The study sample consisted of 50 anemic women with vitamin D deficiency and 50 healthy women with normal hemoglobin and sufficient serum vitamin D levels. Restriction fragment length polymorphism (RFLP) analysis of the VDR genes was done for Single Nucleotide Polymorphism (SNP) sites namely ApaI, BsmI and TaqI. Statistical correlation was done between gene polymorphisms at these three sites and hemoglobin levels. Results: We found a significant association between TaqI site polymorphisms of the VDR gene and presence of anemia in the study population. Conclusion: This is the first report of a significant association between vitamin D receptor gene polymorphisms and anemia in saudi population. Further studies on a larger population size will pave way to elucidation of the mechanism in which VDR gene polymorphisms exert an influence on anemia.